The Noble Values of Riau Tunjuk Ajar Melayu and Their Implications for Multicultural Counseling - Restiafandi, Wahyu; Eddy Wibowo, Mungin; Awalya, Awalya (Jurnal Bimbingan Konseling, 2023)
Multicultural Counseling is a counseling concept which accommodates cultural differences so that the counseling process can be accepted by counselees. This study attempted to describe the noble values in the Riau Tunjuk Ajar Melayu and their implications for multicultural counseling services. It used a qualitative method with the design of narrative ethnography, while the fordata collection, documentations and interviews were conducted. In addition, the ethnographic phenomena were further revealed using a content analysis, including: description, analysis, and interpretation. Findings showed that the noble values of Riau Tunjuk Ajar Melayu reflected the attitudes of openness and pluralism acceptance practiced by the Melayu society in Riau. Meanwhile, the values also portrayed the practice of multicultural values in the way they present a mentally healthy human figure who is humble, trustworthy, self-aware, confident, and having a sense of shame. Again, the values are universal and can be applied not only by counselors in multicultural counseling services, but also counselees to become good individuals according to the culture of the Riau Malay society.